Recent advances in understanding the neurobiology of childhood socioeconomic disadvantage - Holz, Nathalie E.; Laucht, Manfred; Meyer-Lindenberg, Andreas (Current opinion in psychiatry, 2015)
To provide an update of recent research regarding neural mechanisms of socioeconomic disadvantage. The studies reviewed provide convincing evidence of the detrimental effects of early adversities on brain structure and function. The effects of socioeconomic disadvantage and related environmental risks, such as childhood adversity and smoking during pregnancy, while affecting distributed networks of brain regions, have decreased prefrontal activity and volume as a common feature. Recent work suggests that socioeconomic disadvantage and related risk factors may account for a significant proportion of variance in measures of brain structure and function, which may mediate the increased risk of psychopathology. Impaired prefrontal control may be a convergent mechanism underlying early exposure to socioeconomic risk factors in humans. Environmental imaging, that is, the impact which environmental adversity may have on brain structure and function, has only recently moved into the focus of interest. This is surprising because the link to psychopathology has long since been acknowledged and socioeconomic risk factors are modifiable, meaning that understanding their mechanism may point toward prevention and early intervention mechanisms. In future work, the interplay between different environmental risk factors, their potential epigenetic mechanisms, and their interaction with genetic risk should be studied.